2018
DOI: 10.1016/j.jsb.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlative imaging reveals physiochemical heterogeneity of microcalcifications in human breast carcinomas

Abstract: Microcalcifications (MCs) are routinely used to detect breast cancer in mammography. Little is known, however, about their materials properties and associated organic matrix, or their correlation to breast cancer prognosis. We combine histopathology, Raman microscopy, and electron microscopy to image MCs within snap-frozen human breast tissue and generate micron-scale resolution correlative maps of crystalline phase, trace metals, particle morphology, and organic matrix chemical signatures within high grade du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 63 publications
6
54
0
Order By: Relevance
“…The mineralized particle sizes reported here ranged from sub-micron to 20 μm, below the resolution limit of mammography. Similar sizes of MCs were recently reported in human breast tumor tissue samples and could represent early stages of mineralization that then grow to the larger sizes detected by mammography[15]. 3D localization of sub-micron particles within the spheroids, however, will require the use of higher resolution volume techniques, such as Focused Ion Beam-Scanning Electron Microscopy imaging[64,65].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The mineralized particle sizes reported here ranged from sub-micron to 20 μm, below the resolution limit of mammography. Similar sizes of MCs were recently reported in human breast tumor tissue samples and could represent early stages of mineralization that then grow to the larger sizes detected by mammography[15]. 3D localization of sub-micron particles within the spheroids, however, will require the use of higher resolution volume techniques, such as Focused Ion Beam-Scanning Electron Microscopy imaging[64,65].…”
Section: Discussionsupporting
confidence: 61%
“…Our SEM data (Fig. 2a–c) and previous results[15], however, showed that mineralization also occurs in core areas, both in vitro and in tissues. MCs in the core most likely form by unregulated mineralization[56–59], but possibly via a dysregulated process followed by cell death.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This association of breast mineralization to cancer has, therefore, led to a number of research initiatives aiming to identify specific differences between benign and malignant mineralization [125,126,127]. Through electron and light microscopy, X-ray diffraction, and microprobe analysis, two chemically different types of minerals were associated with breast carcinomas: calcium oxalate and apatite [13,14]. Calcium oxalate has been identified mostly in the context of benign diseases [128], although some recent studies failed to identify its presence [129].…”
Section: Breast Tissue Mineralizationmentioning
confidence: 99%